![]() |
Home | Teacher | Parents | Glossary | About Us | |||||||||||
![]() |
|||||||||||
|
|||||||||||
|
![]() |
|
3 Proofs
Proof of Given:
= = [e^(n ln x)] [n/x] = x^n n/x = n x^(n-1) Q.E.D. Proof of Given:
1/n
Proof of Given: (a+b)^n = (n, 0) a^n b^0
+ (n, 1) a^(n-1) b^1 + (n, 2) a^(n-2)
b^2 + .. + (n, n) a^0 b^n Solve:
= lim [ x^n + (n, 1) x^(n-1) d + (n, 2) x^(n-2) d^2 + .. + x^0 d^n - x^n ] / d = lim [ (n,1) x^(n-1) d + (n, 2) x^(n-2) d^2 + .. + x^0 d^n ] / d = lim (n,1) x^(n-1) + (n, 2) x^(n-2) d + (n, 3) x^(n-3) d^2 + .. + x^0 d^n = lim (n, 1) x^(n-1) (all terms on right cancel out because of the d factor) = lim (n, 1) x^(n-1) = n! / ( 1! (n-1)! ) x^(n-1) = n x^(n-1) QED |
|
|||||||||||||||||
|